Prenatal and early-life air pollutant exposure and epigenetic aging acceleration - Lee, Dong Wook; Lim, Youn Hee; Choi, Yoon Jung; Kim, Soontae; Shin, Choong Ho; Lee, Young Ah; Kim, Bung Nyun; Kim, Johanna Inhyang; Hong, Yun Chul (Ecotoxicology and Environmental Safety, 2024)
Background: This study investigated the association of prenatal and early childhood exposure to air pollution with epigenetic age acceleration (EAA) at six years of age using the Environment and Development of Children Cohort (EDC Cohort) Materials & methods: Air pollution, including particulate matter [< 2.5 µm (PM2.5) and < 10 µm (PM10) in an aerodynamic diameter], nitrogen dioxide (NO2), ozone (O3), carbon monoxide (CO), and sulfur dioxide (SO2) were estimated based on the residential address for two periods: 1) during the whole pregnancy, and 2) for one year before the follow-up in children at six years of age. The methylation levels in whole blood at six years of age were measured, and the methylation clocks, including Horvath's clock, Horvath's skin and blood clock, PedBE, and Wu's clock, were estimated. Multivariate linear regression models were constructed to analyze the association between EAA and air pollutants. Results: A total of 76 children in EDC cohort were enrolled in this study. During the whole pregnancy, interquartile range (IQR) increases in exposure to PM2.5 (4.56 μg/m3) and CO (0.156 ppm) were associated with 0.406 years and 0.799 years of EAA (Horvath's clock), respectively. An IQR increase in PM2.5 (4.76 μg/m3) for one year before the child was six years of age was associated with 0.509 years of EAA (Horvath's clock) and 0.289 years of EAA (Wu's clock). PM10 (4.30 μg/m3) and O3 (0.003 ppm) exposure in the period were also associated with EAA in Horvath's clock (0.280 years) and EAA in Horvath's skin and blood clock (0.163 years), respectively. Conclusion: We found that prenatal and childhood exposure to ambient air pollutants is associated with EAA among children. The results suggest that air pollution could induce excess biological aging even in prenatal and early life.
Keywords: Aging; Air Pollutants; Air Pollution; Carbon Monoxide; Child; China; Cohort Studies; DNA Methylation; Environmental Exposure; Epigenesis, Genetic; Female; Humans; Male; Maternal Exposure; Nitrogen Dioxide; Ozone; Particulate Matter; Pregnancy; Prenatal Exposure Delayed Effects; Air pollution; Child; Cohort studies; DNA methylation; Epigenetic age